Mortality in children from influenza and respiratory syncytial virus. Issue 7 (17th June 2005) - Fleming, Douglas M; Pannell, Rachel S; Cross, Kenneth W
Abstract : Study objective: To quantify mortality attributable to influenza and respiratory syncytial virus (RSV) infection in children. Design and methods: Comparison of death rates (all cause and certified respiratory) in England over winters 1989/90 to 1999/00 during and outside influenza and RSV circulation periods. Virus active weeks were defined from clinical and virological surveillance data. Excess deaths associated with weeks of either influenza or RSV activity over virus non-active weeks were estimated in each winter for age groups 1–12 months, 1–4, 5–9, and 10–14 years. The estimate obtained was allotted to influenza and RSV in the proportion derived from independent separate calculations for each virus. Main results: Average winter respiratory deaths attributed to influenza in children 1 month–14 years were 22 and to RSV 28; and all cause deaths to influenza 78 and to RSV 79. All cause RSV attributed deaths in infants 1–12 months exceeded those for influenza every year except 1989/90; the average RSV and influenza attributed death rates were 8.4 and 6.7 per 100 000 population respectively. Corresponding rates for children 1–4 years were 0.9 and 0.8 and for older children all rates were 0.2 or less, except for an influenza rate of 0.4 in children 10–14 years. Conclusions: Influenza and RSV account for similar numbers of deaths in children. The impact varies by winter and between age groups and is considerably underestimated if analysis is restricted to respiratory certified deaths. Summing the impact over the 11 winters studied, compared with influenza RSV is associated with more deaths in infants less than 12 months, almost equal numbers in children 1–4 years, and fewer in older children. Improved information systems are needed to investigate paediatric deaths.